Looks and Gaming: Who and Why? - Andy Chung; Daniel S. Hamermesh; Carl Singleton; Zhengxin Wang; Junsen Zhang (Institute of Labor Economics (IZA), 2024)
We investigate the relationship between physical attractiveness and the time people devote to video/computer gaming. Average American teenagers spend 2.6% of their waking hours gaming, while for adults this figure is 2.7%. Using the American Add Health Study, we show that adults who are better-looking have more close friends. Arguably, gaming is costlier for them, and they thus engage in less of it. Physically attractive teens are less likely to engage in gaming at all, whereas unattractive teens who do game spend more time each week on it than other gamers. Attractive adults are also less likely than others to spend any time gaming; and if they do, they spend less time on it than less attractive adults. Using the longitudinal nature of the Add Health Study, we find supportive evidence that these relationships are causal for adults: good looks decrease gaming time, not vice-versa.
Keywords: J22; L82; L86; 330; physical attractiveness; beauty; time allocation; social activity; teenage behavior